2020
DOI: 10.1016/j.ajem.2020.05.100
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocarditis associated with COVID-19 infection

Abstract: We present the case of a 20-year-old male patient without previous history of cardiovascular disease who was admitted to our hospital with a new onset febrile sensation and chest pain. Chest computed tomography revealed a subpleural consolidation with a halo of ground-glass opacification. Blood tests revealed elevated levels of markers of myocyte necrosis (troponin I and creatine kinase-MB). Nasopharyngeal swab was positive for COVID-19. Cardiac MRI showed myocardial edema and late gadolinium enhancement compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 10 publications
2
49
0
2
Order By: Relevance
“…pneumonia. Early reports have indicated that fulminant myocarditis may occur in SARS-CoV-2 infection, contributing significantly to morbidity of COVID-19 [ [29] , [30] , [31] , [32] , [33] , [34] ]. In addition, acute lymphocytic myocarditis has been demonstrated in endomyocardial biopsies of patients with clinically suspected SARS-CoV-2 associated myocarditis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…pneumonia. Early reports have indicated that fulminant myocarditis may occur in SARS-CoV-2 infection, contributing significantly to morbidity of COVID-19 [ [29] , [30] , [31] , [32] , [33] , [34] ]. In addition, acute lymphocytic myocarditis has been demonstrated in endomyocardial biopsies of patients with clinically suspected SARS-CoV-2 associated myocarditis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those with a severe and depressed LV function developed cardiogenic shock, thereby having a worse prognosis 4,6 . Although CMR was not performed in all cases because of prolonged acquisition time and the fact that COVID-19 infection is highly contagious, it showed myocardial edema and sub-epicardial late gadolinium enhancement in some parts of the LV [7][8][9][10][11][12]16 . Interestingly, no EMB was performed to confirm the diagnosis in all patients even though it is considered a gold standard.…”
Section: Imaging Featuresmentioning
confidence: 99%
“…21 Presenting symptoms are broad and nonspecific, including fatigue, chest discomfort, dyspnoea, heart failure as well as fulminant myocarditis with hemodynamic instability. [22][23][24][25][26][27][28][29][30][31][32][33] Patients are often found to have ST-T wave changes on electrocar- 7 The systemic inflammation and catecholamine surge caused by COVID-19 also increases plaque vulnerability and rupture. 7,35 In a case series conducted by Bangalore et al, 18 patients with COVID-19 with ST-segment elevation on electrocardiogram indicating potential acute myocardial infarction were studied.…”
Section: Acute Myocarditismentioning
confidence: 99%